2018
DOI: 10.1002/hyp.13263
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of groundwater with Lake Urmia in Iran

Abstract: Being a large hyper‐saline water body, Lake Urmia in north‐western Iran deals with a gradual decline in its water level. Most of the studies on Lake Urmia have neglected the groundwater issue. In this study, as a direct approach, the interaction between the groundwater level and the lake water level is investigated both in time and space by analysing the groundwater data compiled from observation wells surrounding the lake. Baseflow separation is considered as an indirect approach to understand the groundwater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…For instance, hydrochemical investigations at the western shore indicated almost no direct hydraulic interaction between groundwater and lake water 30 , another study considered a direct component to be less than 3% of total inflow 7 , and some studies provide even quantitative estimates ranging from about 60 × 10 6 m 3 a −1 to 210 × 10 6 m 3 a −1 29,31,32 . The reason for these rather low rates is the fact that the main receiving water bodies for the groundwater are the perennial rivers discharging into the lake 1,7,32,33 . Therefore, a direct groundwater component is neglected in the water balance of the lake, Eq.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, hydrochemical investigations at the western shore indicated almost no direct hydraulic interaction between groundwater and lake water 30 , another study considered a direct component to be less than 3% of total inflow 7 , and some studies provide even quantitative estimates ranging from about 60 × 10 6 m 3 a −1 to 210 × 10 6 m 3 a −1 29,31,32 . The reason for these rather low rates is the fact that the main receiving water bodies for the groundwater are the perennial rivers discharging into the lake 1,7,32,33 . Therefore, a direct groundwater component is neglected in the water balance of the lake, Eq.…”
Section: Resultsmentioning
confidence: 99%
“…In its standard version, WaterGAP is calibrated against observed mean annual river discharge at 1319 stations worldwide by adjusting 1-3 model parameters related to runoff generation and streamflow (Müller Schmied et al, 2014), but due to lack of data not for any station in Lake Urmia basin. A previous WaterGAP version was calibrated, for 22 large basins, against streamflow and total water storage anomalies by adjusting 6-8 parameters (Werth and Güntner, 2010). WGHM can be run globally or for a specific basin.…”
Section: Watergapmentioning
confidence: 99%
“…This has led to increase in the irrigation hence less available runoff as for the lake inflow, and also caused a major increase in evapotranspiration. The following sentence (last sentence of the paragraph) does not explicitly indicate the greater role of human activities in the lake desiccation compared to atmospheric climate change, which is the common finding of the most of the studies in this area [AghaKouchak et al, 2015;Aneseh et al, 2018;Stone, 2015;Torabi Haghighi et al, 2018;Vaheddoost and Aksoy, 2018]. On P 24 L 34 you concluded that "climate change must be constrained to prevent strong decreases of precipitation and runoff".…”
Section: Discussion Of Modelling Results and Equifinalitymentioning
confidence: 99%